Treatment of spent engine oil (spent SAE W50) via solvent extraction- adsorption process for the production of transfer oil: Physico-chemical properties of the adsorbents - I.J., Ani (2023)
Regeneration of base oil from spent engine oil (spent SAE W50) for transfer oil production has been investigated using the solvent extraction-adsorption method. Solvent treated base oil regenerated from spent SAE W50 was treated with activated carbon (AC) from Penthaclatra macophylla pod (PMP) and activated clay (ACL) from Ukpor clay. The oil was characterized before and after treatment for heavy metals content, kinematic viscosity, viscosity index, specific gravity, and pour point. The carbon and clay were characterized using FTIR, BET, SEM-EDX, XRF, and XRD. Characterization results revealed the required properties of the adsorbents that make them capable of adhering impurities to their active sites. Results obtained showed that the optimum conditions for the regeneration of base oil from spent SAE W50 was a temperature of 110 °C, an adsorbent dosage of 5% w/v and a contact time 60 min, with 98% removal of impurities using the mixture of AC and ACL (AC-ACL). The transfer oil was obtained using a blend of the recovered base oil and virgin oil (150 N) at the ratio of 1:1.2. The blend gave the required properties for a transfer oil of similar quality to ISO VG 46.